A Generic Review of Web Technology: DJango and Flask - Idris, Nuruldelmia; Mohd Foozy, Cik Feresa; Shamala, Palaniappan (International Journal of Advanced Science Computing and Engineering, 2020)
The research is discussing the relevance of web technology based on its history, current development, future working process, threats, or attacks that are common in web technology, and its solutions to encounter the threats. Nowadays, web services have become one of the most vital components in peoples' daily lifestyle. People are talking how the advancement in the technology leads the world now. The evolution of network has triggered the demands especially in internet connection as everyone around the world are depending on the connection to do their activities especially for communication. It is required to have high speed internet and bandwidth to prevent poor connection. Besides that, due to advance development in computing products and network, people enables to catch up with the current trends which spark the existence of web development that are used to gather information.